Navigating Challenges: Students’ Strategies for Overcoming English Speaking Difficulties - Riyadh Ahsanul Arifin; Revi Nur Ridwan; Eva Meidi Kulsum (Mathematics Education Study Program, 2025)
This study investigates the strategies used by junior high school students to overcome difficulties in speaking English. Through qualitative interviews with twelve eighth-grade students at a junior high school in Bandung, this research identifies common strategies employed by students to address these challenges. The strategies include preparation before speaking, expanding vocabulary through music, reading English texts, studying grammar, and integrating information and communication technology (ICT) tools like Duolingo. The findings suggest that preparation helps students organize thoughts and reduce anxiety, while vocabulary expansion and grammar study are key for effective communication. ICT, particularly Duolingo, plays a significant role in enhancing speaking skills by providing interactive and engaging platforms for practice. These results inferred that educators can use these insights to adopt more effective teaching methods, while students can apply these strategies to boost their confidence and speaking abilities.